Board composition, board diversity and stock performance - CHIRAPHOL, Chiyachantana N. (Institutional Knowledge at Singapore Management University, 2021)
The study investigates the relationship between six board compositions and stock returns. The results indicate a significant association between various board compositions and stock returns. Specifically, board size and executive directors have a negative impact, whereas independent directors enhance stock returns. Busy directors positively impact the abnormal stock returns for the companies in the non-financial industry, which implies that busy directors who serve on more boards tend to be well connected. More importantly, the results indicate a significant positive relationship between board tenure and stock returns. Board service time is perceived as the board quality of knowledge and experience from the investors’ point of view.